2012 International Conference on Microwave and Millimeter Wave Technology (ICMMT) 2012
DOI: 10.1109/icmmt.2012.6230016
|View full text |Cite
|
Sign up to set email alerts
|

A LTCC-based Ku-band 3D bandpass filter using stepped-impedance hairpin resonators

Abstract: A new compact bandpass filter using stepped impedance (SI) hairpin resonators with multilayer configuration based on LTCC technology for Ku-band application is proposed. Two pairs of transmission zeros are achieved by introducing the cross coupling and asymmetric I/O structure, which can improve the rejection in the stop band. The compact filter is designed as a three-dimension structure which is embedded in the ceramic substrate based on the LTCC multilayer manufacturing technology. EM simulator HFSS is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The improved BPF has a size of 6 3 6 mm 2 (including 50-X feed lines), which is compact amounting to approximately 0.52k g 3 0.52k g , where k g is the guide wavelength at 17 GHz. Comparing with other similar works presented in the Table 1 [8][9][10], it is shown that the improved BPF in this work has better rejection at upper stopband and smaller size.…”
Section: Improved Filter Designing To Enhance the Selectivitysupporting
confidence: 59%
See 1 more Smart Citation
“…The improved BPF has a size of 6 3 6 mm 2 (including 50-X feed lines), which is compact amounting to approximately 0.52k g 3 0.52k g , where k g is the guide wavelength at 17 GHz. Comparing with other similar works presented in the Table 1 [8][9][10], it is shown that the improved BPF in this work has better rejection at upper stopband and smaller size.…”
Section: Improved Filter Designing To Enhance the Selectivitysupporting
confidence: 59%
“…Measured results show the improved BPF have good selectivity and wide stopband, so that it can be used for wireless communication and radar applications. [9] 2.54% -0.5k g by k g [10] 5.2% 16-38 GHz 0.75k g by 0.5k g This work 17.3% 22.6-50 GHz 0.53k g by 0.53k g…”
Section: Resultsmentioning
confidence: 81%
“…To achieve this goal, the Ku-band bandpass filters have become one of the most important circuit components. There are many methods proposed to design Ku-band bandpass filters [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The substrate integrated waveguides provide easy integration of planar circuits with the waveguide, while still maintaining low loss and high power handling capability of the waveguide. Due to these advantages, a variety of RF bandpass filters have been realized using SIW technology [2,3]. In [2], a novel compact Ku-band bandpass filter based on substrate integrated circular cavities is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation